The set of equations 3x - 2y = 3 and x + 4y - 6 = 0 has to be solved.

x + 4y - 6 = 0

=> x = 6 - 4y

Substitute in 3x - 2y = 3

=> 3(6 - 4y) - 2y = 3

=> 18 - 12y - 2y = 3

=> 14y = 15

=> y = 15/14

x = 12/7

**The solution of the system of equations is x = 12/7 and y = 15/14**

3x - 2y = 3 and x + 4y - 6 = 0

x + 4y - 6 =0

subtract 4y and add 6

x = -4y + 6

you now have x

substitute it as x

3(6 - 4y) - 2y = 3

18 - 12y - 2y = 3

combine like terms

-14y = -15

divide by -14

y = 1.07

plug in the number as y:

x + 4(1.07) - 6 = 0

x + 4.3 - 6 = 0

x - 1.7 = 0

x = 1.7

3x - 2y = 3 and x + 4y - 6 = 0

x + 4y - 6 =0

subtract 4y and add 6

x = -4y + 6

plug in the number as x

3(6 - 4y) - 2y = 3

18 - 12y - 2y = 3

move like terms to the same side

-12y - 2y = 3 - 18

-14y = -15

y = 15/14 or 1.07

plug in the number as y:

x + 4(15/14) - 6 = 0

x + 4.3 - 6 = 0

x - 1.7 = 0

x = 1.7